IN SILICO PREDICTION OF BIOACTIVE TARGET CLASSES AND ADMET PROFILE OF CAPSAICIN WITH RELEVANCE TO DAYAK CHILI (Capsicum frutescens L.) - Yuneka Saristiana; Fendy Prasetyawan; Lisa Savitri (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2026)
Capsaicin is a well-known bioactive compound present in various Capsicum species, including Dayak chili (Capsicum frutescens L.). This study aimed to predict the bioactive target classes and ADMET profile of capsaicin using an in silico approach. The chemical structure of capsaicin was retrieved from the PubChem database and analyzed using SwissTargetPrediction, SwissADME, and pkCSM platforms. The prediction results indicated that capsaicin interacts with multiple protein classes, including oxidoreductases, cytochrome P450 enzymes, voltage-gated ion channels, G-protein-coupled receptors, hydrolases, phosphatases, kinases, and membrane receptors. High-probability predicted targets included PTGS1, CYP1A2, TRPV1, CNR1, and FAAH, suggesting potential anti-inflammatory, analgesic, neuromodulatory, and metabolic regulatory effects. ADMET analysis demonstrated favorable absorption and distribution characteristics, with predicted hepatotoxicity and hERG II inhibition requiring further investigation. These findings represent computational predictions and should be interpreted cautiously, as in silico results require further experimental validation. Capsaicin demonstrates multi-target potential that may support future pharmacological development and experimental studies.